Correction of a Class III Malocclusion with a Functional Shift and Severe Crowding - Yahya A. Alogaibi; Ahmad A. Al-Fraidi; Manar K. Alhajrasi; Ali A. Hassan (Case Reports in Dentistry)
A forward functional shift of the mandible is a significant problem that can cause both functional and aesthetic complications for many patients. This shift usually occurs in growing patients, and it is unusual to see in adult patients. This case report shows an adult patient with a forwarding functional shift that caused both anterior and posterior crossbites with a pseudo class III dental and skeletal relationship. The patient also showed severe upper arch crowding with blocked-out canines and mild crowding in the lower arch. The treatment of this patient involved extraction of the upper right and left first premolars and the lower right first premolar, followed by opening of the bite to relieve the neuromuscular reflex of the forward protrusion of the mandible during centric occlusion and to correct both the anterior and posterior crossbites. Extraction spaces were closed using class III elastics and elastomeric chains. At the end of the treatment, good functional and aesthetic results were obtained after the elimination of the forward functional shift.